Evaluating Teacher Performance Based On Gender Using The Charlotte Danielson Evaluation Model - Iriani, Ade; Lelatobur, Lovely Ezverenzha (STKIP Singkawang, 2024)
The objective of this research is to assess teacher performance in public senior high schools in the Maluku Barat Daya (MBD) district, with a focus on gender as a variable. Four primary components were utilized to evaluate teacher performance, which include lesson planning and preparation, class management, lesson implementation, and professional responsibility. Data were gathered from a total of twelve teachers, comprising six females and six males, employing the Charlotte Danielson Evaluation Model. The research employed a mixed-methods approach, initially utilizing qualitative methods such as interviews, observations, and document analysis, followed by quantitative analysis using the Charlotte Danielson model performance assessment rubric questionnaire. The outcomes indicated that both female and male teachers exhibited strong skills in lesson planning and design. In terms of class management, female teachers demonstrated excellent performance, whereas male teachers exhibited good performance. In the aspect of lesson implementation, female teachers displayed excellent performance, while male teachers were rated as good. Professional responsibility was assessed as good for both gender groups. The conclusion drawn is that gender does have an impact on teacher performance in terms of class management and lesson implementation.